Znotrajbolnišnični transport kritično bolnih bolnikov - Jereb, Sara (Obzornik zdravstvene nege, 2015)
Introduction: Intrahospital transport of critically ill patients is indicated when the expected benefits of the procedure outweigh the risks related to transportation. The purpose of this article is to demonstrate the adverse events associated with the transport, and the procedures that can reduce their incidence. Methods: A descriptive research method was used in the study which was founded on the review of previous research and guidelines. The data were retrieved from the PubMed database, Google search engine and COBIB.SI- the cooperative bibliographic/catalogue database. The search was limited to the foreign literature published in last five years and the Slovenian literature published in the last decade. Results: The most important risk factors for complications linked to patient transport are considered in the selected research. The studies included can be compared in terms of the incidence of the most common complications and solution planning, but not in terms of the number of patients involved. The research included only the incidents which occurred in the teaching or university hospitals. None of the authors reported higher, transport-related mortality. Discussion and conclusion: In spite of differences in the nature of complications, the results are comparable. The common equipment-related adverse events could be prevented by taking appropriate measures. Under time pressure, the risk of complications is increased by noncompliance to the adopted guidelines for intrahospital transport.
Keywords: bolniki; incidenti; incidents; patients; premestitve; relocations; zapleti